An assessment of the implementation of the KwaZulu-Natal 365 Days Policy Framework for the Eradication of Gender-Based Violence focusing on victim support to Indian women living in the flat-dwelling areas of Westcliff, Chatsworth - Wielenga, Cori (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2022.